Spatiotemporal analysis of the structure and genetic diversity of Stemphylium vesicarium populations in New York onion fields - Subedi, Aastha; Heck, Daniel W.; Hay, Frank; Piñeros-Guerrero, Natalia; Pethybridge, Sarah J. (Frontiers in Microbiology, 2025)
Stemphylium leaf blight (SLB), caused by the hemibiotrophic fungus, Stemphylium vesicarium, is the dominant foliar disease affecting onions in New York (NY), USA. The development of integrated disease management strategies for SLB is challenged from the lack of information surrounding phylodynamics and evolutionary patterns of the causal organism. This study evaluated the spatiotemporal patterns of genetic diversity, differentiation and population structure of 210 S. vesicarium isolates from populations collected over 6 years (2016 to 2022) across five onion production regions in NY using nine microsatellite loci. A total of 158 multilocus genotypes (MLGs) were identified among the 210 isolates, indicating high genetic diversity and genotypic variation. Low genetic differentiation was observed across spatial and temporal populations, with greater genetic variation within populations than between them. Population structure analyses using multiple approaches revealed no clear temporal or spatial genetic patterns, although isolates from 2016 and the Orange County region showed some genetic divergence. Additionally, significant linkage disequilibrium among loci suggested a predominantly clonal population structure in all regions, except the Finger Lakes, which displayed non-significant linkage disequilibrium. These findings highlight the complex population biology and dynamics of S. vesicarium, characterized by high genetic diversity, admixture, and mixed reproduction modes and emphasize the challenges in managing SLB, as these characteristics can enable rapid population adaptation to diverse environmental conditions and management practices.